2021
DOI: 10.3389/fped.2021.629346
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes Correlate With Metabolic Syndrome, Inflammation, and Endothelial Dysfunction in Prepubertal Children With Obesity

Abstract: Background: Metabolic syndrome (MetS) can start in children with obesity at very young ages. Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic component of metabolic syndrome. If left untreated, the clinical course of NAFLD can be progressive and can become chronic if not detected at an early stage.Objective: We aimed to quantify the differences in liver enzymes between prepubertal children with obesity and children with normal weight to determine any associations between them and param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…These findings are consistent with previous publications stating that obesity is the most frequent cause of hypertransaminasemia in both adults and children ( 20 ). In a cross-sectional study, prepubertal children with obesity were shown to have higher values for transaminase activities than children with normal weight ( 26 ). In another study with 234 obese children aged 6 years and older, 40% even suffered from Non-alcoholic Fatty Liver Disease ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous publications stating that obesity is the most frequent cause of hypertransaminasemia in both adults and children ( 20 ). In a cross-sectional study, prepubertal children with obesity were shown to have higher values for transaminase activities than children with normal weight ( 26 ). In another study with 234 obese children aged 6 years and older, 40% even suffered from Non-alcoholic Fatty Liver Disease ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, lower level of serum exosomal miR-320d was found in hepatocellular carcinoma ( 42 ). Based on these evidences, dyslipidemia seems then to moderately contribute to the LD associated dysregulation of cmiR-320 b, while liver dysfunction and inflammation, abundantly interrelated conditions ( 43 ), seem to predict the downregulation of cmiR-320d.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas (17) reports that serum cholinesterase activity may be increased in the patients with hepatic steatosis, diabetes mellitus and patients with hyperlipoproteinaemia type IV. Ramirez-Jimenez et al (18), Han et al (19) and Valle-Martos et al (20) described a positive association of an increased plasma BChE activities with triacylglycerols, total cholesterol, LDL-cholesterol, lower HDLcholesterol and metabolic syndrome. The results of the examination of BChE activity in our group of patients with NAFLD showed that the activity of BChE was signifi cantly increased.…”
Section: Discussionmentioning
confidence: 99%